FEATURES OF THE SOCIAL IDENTITY OF UKRAINIANS - Alla KOVALENKO; Kateryna BEZVERKHA (Moldova State University, 2018)
The paper analyses the theoretical principles of the features of social identity, which made it possible to study deeply the problem of group membership, based on a questionnaire on social identity. The basis of the research is the theory   P.P. Bellini [1], in which the emergence of social identity occurs from the moment of birth under the influence of the parent's family, but the maximum development it acquires during the interaction of rights in society, which later allows you to talk about changes in the relevance of the one or another structural characteristic of social identity. The family is in the first place in significance, which gives the person support for the realization of their own needs and self-development through membership in the group. But intercollective relationships are also significant, this makes it possible to find satisfaction, despite the strong sense of competition that arises. The article reveals the age-old peculiarities of the transformation of social identity. It shows that with age, a person does not lose the need to identify himself with a particular social group, which gives her a sense of satisfaction from staying in it. Satisfaction of this need allows it to better reveal its potential in self-knowledge and self-development, as well as to realize itself in the system of group relations. Each age group has its own traits, which characterize the formation of a person as a social person. That is, with growing up and gaining responsibility for the establishment of one's own career, family, political and cultural views, social identity is updated, which is subsequently not dull, but transformed into a desire to meet their own needs through the group without its structural connections, intergroup relations, and based on the experience gained. CARACTERISTICI ALE IDENTITĂȚII SOCIALE A UCRAINENILOR În articol sunt analizate principiile teoretice fundamentale în studiul identității sociale, care au stat la baza investigării apartenenței de grup. Investigația se bazează pe teoria lui P.P. Bellini [1], conform căreia constituirea identității sociale începe din momentul nașterii, suportând influențele mediului familial. Insă, influențele decisive în dezvoltarea identității se produc prin intermediul interacțiunilor societale, care ne permit să vorbim despre schimbările relevante produse în structura identității sociale. Familia este prima în ordinea semnificației, fiind mediul care îi oferă individului suport pentru realizarea trebuințelor și a dezvoltării de sine, prin apartenența la acest grup. Însă, relațiile intergrupale sunt la fel de importante, relațiile cu ceilalți oferindu-i persoanei prilejul de a trăi stări de satisfacție, în pofida competiției care caracterizează, în fapt, relațiile intergrupuri. În articol sunt evidențiate inflluențele pe care le exercită vârsta persoanelor asupra identității sociale. Rezultatele arată că, odată cu vârsta, nevoia de apartenență la un grup rămâne la fel de importantă, prilejuind indivizilor stări de satisfacție urmare a afilierii la un grup. Satisfacerea nevoii de afiliere favorizează cunoașterea de sine și dezvoltarea personală, implicit realizarea în cadrul grupului. Fiecare perioadă de vârstă își lasă amprenta asupra formării individului ca persoană socială. Astfel, odată cu creșterea individului, pe măsura responsabilizării acestuia pentru dezvoltarea unei cariere profesionale, crearea familiei, formarea convingerilor politice și culturale, identitatea socială este revizuită continuu, acest fapt fiind un mod de realizare a intereselor individuale în cadrul grupului, dar fără a fi influențați de conexiunile structurale ale grupului și de relațiile intergrupale, ci având la bază experiența acumulată.